Stakeholders’ planning workshop for the Rwanda Climate Services for Agriculture project - Munyangeri, Yvonne Uwase; Mungai, Catherine (2017)
This report summarizes the proceedings of the stakeholders’ planning workshop for the Rwanda Climate Services for Agriculture project held in Kigali, Rwanda on 6-7 March 2017. Organized by the project team at the International Centre for Tropical Agriculture (CIAT), the meeting brought together 39 participants from various institutions including the International Research Institute for Climate and Society (IRI), the International Livestock Reaserach Institute (ILRI), the World Agroforestry Center (ICRAF), the University of Reading, Meteo Rwanda, the Rwanda Agricultural Board (RAB), the Ministry of Agriculture, Development Rural du Nord (DERN), Radio Huguka, AICP and CARITAS. Participants discussed project achievements and activities for year 1 of the project and identified activities for the year 2 of the project.